2019
DOI: 10.1111/cp.12136
|View full text |Cite
|
Sign up to set email alerts
|

External Shame as a Mediator between Paranoia and Social Safeness in Psychosis

Abstract: Background: The overactivation of the threat-defence system combined with an underdeveloped affiliative system has been emphasised as important in psychosis, usually leading to negative affect and impaired social functioning. Difficulties in feeling safe and content in relationships with others, common in individuals with psychotic symptoms, have been linked to two specific outputs of the threat-defence system: Paranoid ideation and external shame. This study sought to explore the associations between paranoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 52 publications
2
12
0
Order By: Relevance
“…Shameful feelings in response to deliberate harm are more consistent with activation of negative schemas about the self (“Bad Me” paranoia) rather than the protection against distress from others (“Poor Me” paranoia) ( 53 ). Shame is strongly associated with the frequency and distress of paranoid thinking in patients with psychotic disorders ( 54 ), although less is known about its relationship with the content of delusions. As the PDI contains some items of persecution, suspiciousness, and paranoid ideas, it is possible that multidimensional delusional beliefs, including thoughts of persecution, predict shame in response to interpersonal harm.…”
Section: Discussionmentioning
confidence: 99%
“…Shameful feelings in response to deliberate harm are more consistent with activation of negative schemas about the self (“Bad Me” paranoia) rather than the protection against distress from others (“Poor Me” paranoia) ( 53 ). Shame is strongly associated with the frequency and distress of paranoid thinking in patients with psychotic disorders ( 54 ), although less is known about its relationship with the content of delusions. As the PDI contains some items of persecution, suspiciousness, and paranoid ideas, it is possible that multidimensional delusional beliefs, including thoughts of persecution, predict shame in response to interpersonal harm.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the measure of affect used in this study included shame, which may have contributed to the strong links found between negative affect and paranoia. Indeed, high shame has been found to increase vulnerability to paranoia in the face of stressful situations (Johnson et al, 2014) and decrease sense of social safeness (Castilho et al, 2017) in clinical populations. Clinically paranoid individuals have been found to experience significantly higher levels of negative cognitions about the self, such as low self-esteem and low self-compassion (Collett et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…There are two described types of shame: internal (focused on the self) and external (focused on others). External shame has been associated with higher levels of paranoia, negative symptoms and post-psychotic distress (Argel, 2018;Birchwood et al, 2007;Castilho et al, 2017;Turner, Bernard, Birchwood, Jackson, & Jones, 2013), on one hand, and difficulties in personal recovery on the other (Wood & Irons, 2016). People with psychotic symptoms have reported higher levels of external shame when compared with non-clinical controls (Keen, George, Scragg, & Peters, 2017).…”
Section: Social Competitive Mentality: the Role Of Shame And Self-cmentioning
confidence: 99%
“…External shame has also been stressed as an important mediator between symptoms and the ability to feel safe and connected in the social world (Argel, 2018;Castilho et al, 2017). Internal shame refers to negative self-evaluations focused on perceived personal mistakes and shortcomings, and thus, a key component of internal shame is self-devaluation and self-criticism (Gilbert & Procter, 2006).…”
Section: Social Competitive Mentality: the Role Of Shame And Self-cmentioning
confidence: 99%
See 1 more Smart Citation